Exploring design considerations for multimodal learning analytics systems: an interview study - Ouhaichi, Hamza; Bahtijar, Vogel; Spikol, Daniel (Frontiers in Education, 2024)
This study explores the perspectives researchers on design considerations for Multimodal Learning Analytics (MMLA) systems. This study focuses on the essential research and development phase that must occur prior to the implementation of MMLA systems. By exploring and identifying reliable design practices, we aim to inform and enhance the effectiveness of MMLA systems in real-world educational settings. In response to the evolving landscape of technology in education, MMLA has emerged, integrating diverse data modalities for real-time insights into student learning processes. In this qualitative study, employing semi-structured interviews, we engaged a diverse group of researchers in the field of MMLA. Through deductive and thematic analysis, we identified key design considerations for MMLA systems. Researchers prioritized ethical considerations universally, emphasizing the responsible handling of multimodal data. The analysis revealed various intersections between considerations affirming and reinforcing existing themes as well as highlighting new emergent considerations. Moreover, we present the MMLA Design Framework (MDF) that was developed based on our findings to guide the process of design and development of MMLA systems. By addressing the lack of conventional practices in MMLA design, we lay the groundwork for subsequent efforts aimed at applying MMLA systems both in research and education. The implications of our findings are important for practitioners and researchers offering practical insights - a set of design considerations and a design framework- for designing and analyzing MMLA systems.